Strengthening the Brand Positioning of Agroedutourism Situ Bolang in Storytelling-Based Sustainable Tourism Development in the Digital Era - Putri, Sindy Yulia; Cahyani, Intan Putri; Hayati, Kumala; Chandra, Bastian; Syadewa, Ian (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
Based on previous research, Situ Bolang is well-suited for the application of the agroedutourism concept. This article explores how the internet can enhance Situ Bolang tourism's public recognition through digital storytelling, which necessitates a compelling narrative to showcase its advantages and attract the interest of potential visitors to visit Situ Bolang. Moreover, the internet has developed digital platforms that can be utilised to enhance the brand positioning of the Situ Bolang agroedutourism area through storytelling. Therefore, the research problem raised is strengthening the brand positioning of Situ Bolang agroedutourism in developing sustainable tourism based on storytelling using digital platforms. In terms of research methodology, this study employed both experimental and participant observation methods. Each approach utilises a SWOT analysis to describe the storytelling strategy. First, a data-driven storytelling strategy describes the strengths and advantages of using the Agroedutourism concept. Second, the philanthropic storytelling strategy explains the development of the idea into a tourist destination that the whole family can visit. Third, a customer-led storytelling strategy addresses the existing threat related to damaged road access. The implementation of all three strategies, as showcased in a YouTube video featuring a character named Bastian, highlights the uniqueness, facilities, and attractions to enjoy at Situ Bolang, as well as conducting interviews to gather testimonials from visitors. This condition certainly strengthens Situ Bolang's brand positioning as a suitable destination for families, thanks to the numerous activities available.